Front Cover Picture: Insight into the Stereocontrol of DNA Polymerase‐Catalysed Reaction by Chiral Cobalt Complexes (Adv. Synth. Catal. 16/2022). Issue 16 (3rd August 2022) - Wu, Ya; Bu, Xinya; Ke, Yongqi; Sun, Huaming; Li, Jingyao; Chen, Lu; Cui, Wei; He, Yujian; Wu, Li
Abstract : The front cover picture, provided by Li Wu and her co‐workers, illustrates stereocontrol of DNA polymerase–catalysed reaction by chiral cobalt complexes, which might seem like "chiral environmental agents". One chiral enantiomer of the cobalt complexes interacts with substrate‐binding site of DNA polymerase, exhibiting inhibition or acceleration of DNA polymerase–catalysed reaction, whereas the other chiral enantiomer does not bind to the key site, causing little effect on the polymerase reaction. Details can be found in the Research Article by Li Wu and co‐workers (Y. Wu, X. Bu, Y. Ke, H. Sun, J. Li, L. Chen, W. Cui, Y. He, L. Wu, Adv. Synth. Catal . 2022, 364, 2760–2771; DOI: 10.1002/adsc.202200418 ).